Execution of Debt Guarantee in Subsidized Housing Credit Agreements Not Based on Deed of Grant of Mortgage Rights (APHT) - Kostiawan, Shaiful; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The legal position of debt collateral in subsidized housing credit agreements that are not based on the Deed of Granting Mortgage Rights (APHT). 2) The procedure for executing debt collateral in subsidized housing credit agreements without APHT according to applicable laws and regulations. This type of research is included in the scope of normative legal research. The approach method in this study is the statute approach. The type of data in this study is secondary data, consisting of primary, secondary and tertiary legal materials. The data collection method was obtained through literature study. The analysis in this study is prescriptive. The results of the study concluded: 1) The legal position of debt collateral in subsidized Home Ownership Credit (KPR) agreements that are not based on the Deed of Granting Mortgage Rights (APHT) is very weak in terms of juridical. Although the Regulation of the Minister of ATR/BPN Number 22 of 2017 provides leniency by allowing the use of a Power of Attorney to Charge Mortgage Rights (SKMHT) until the end of the credit agreement period, this does not change the fact that mortgage rights can only be legally recognized if they are made through an APHT and registered at the Land Office in accordance with the provisions of Law Number 4 of 1996 concerning Mortgage Rights. Without an APHT, the collateral provided by the debtor does not have legal execution power and does not provide perfect property rights for the creditor. 2) The procedure for executing debt collateral in a subsidized mortgage agreement that is not based on a Deed of Granting Mortgage Rights (APHT) cannot be carried out through a direct parate execution mechanism, as regulated in Law Number 4 of 1996 concerning Mortgage Rights. Without an APHT and registration of mortgage rights, the collateral does not have legal standing, so that the creditor does not have preferential rights or execution power over the collateral object. In this condition, the only legal route available to creditors is to seek settlement through a civil lawsuit on the basis of default, which tends to be longer, more complex and riskier.Keywords: Debt Guarantee Execution; Subsidized Housing Credit; KPR.